2019
DOI: 10.1016/j.biocon.2019.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Reintroducing rewilding to restoration – Rejecting the search for novelty

Abstract: Rewilding is emerging as a major issue in conservation. However, there are currently a dozen definitions of rewilding that include Pleistocene rewilding, island rewilding, trophic rewilding, functional rewilding and passive rewilding, and these remain fuzzy, lack clarity and, hence, hinder scientific discourse. Based on current definitions, it is unclear how the interventions described under the rewilding umbrella differ from those framed within the long-standing term 'restoration'. Even projects held up as ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 29 publications
0
47
0
Order By: Relevance
“…Some suggest extending the ‘big tent’ of restoration ecology to include these concepts (Miller & Bestelmeyer, ) whereas others suggest renaming restoration (Rohwer & Marris, ). Now, the misunderstanding of rewilding and its conflation with restoring have caused yet others to go so far as to call for banning the term rewilding (‘a buzz‐word’) from scientific, policy and conservation discourse (Haywood et al, ). Nevertheless, rewilding and restoring stand as distinct concepts, each with its own logical place within the framework of the adaptive cycle (Figure ).…”
Section: Moving Forwardmentioning
confidence: 99%
“…Some suggest extending the ‘big tent’ of restoration ecology to include these concepts (Miller & Bestelmeyer, ) whereas others suggest renaming restoration (Rohwer & Marris, ). Now, the misunderstanding of rewilding and its conflation with restoring have caused yet others to go so far as to call for banning the term rewilding (‘a buzz‐word’) from scientific, policy and conservation discourse (Haywood et al, ). Nevertheless, rewilding and restoring stand as distinct concepts, each with its own logical place within the framework of the adaptive cycle (Figure ).…”
Section: Moving Forwardmentioning
confidence: 99%
“…A dominant component of novel ecosystems is the pervasiveness of introduced species (Hobbs et al 2006), despite invasive species being a leading driver of global biodiversity decline (McKenzie et al 2007;Doherty et al 2016). Therefore, under a rewilding scenario where novel ecosystems are accepted, countries like Australia, for example, will likely be left with European red foxes, Vulpes vulpes, and feral cats, Felis catus, and New Zealand left with stoats, Mustela erminea, and brushtail possums, Trichosurus vulpecula, at the expense of a rich, endemic marsupial and avian fauna, respectively (Towns et al 2013;Hayward et al 2019).…”
Section: What Does This Mean For Rewilding?mentioning
confidence: 99%
“…For example, in a study of wildland managers in the Scottish uplands Deary and Warren (2019) found that all managers valued wildness and biodiversity highly but that there was significant divergence in the interpretations and practices of rewilding, especially with respect to: the value and perceptions of naturalness, the use of management interventions, the value of cultural heritage and traditional land uses, and the place of people within wildland. Hayward et al (2019) have argued that the term 'rewilding' is obsolete and that all existing definitions of rewilding fit within existing definitions of the longer-established field of 'Cores, corridors, carnivores': 'the scientific argument for restoring big wilderness based on the regulatory roles of large predators' (Soulé & Noss, 1998, p. 5) up to 4000 BP, but most are within last 200 years North America Soulé and Noss (1998), Foreman (1999Foreman ( , 2004 and Noss (2003) Pleistocene mega-fauna replacement: 'the restoration of large wild vertebrates into North America in preference to the 'pests and weeds' (rats and dandelions) that will otherwise come to dominate the landscape' (Donlan et al, 2005, p. 913).…”
Section: Definition and Issuesmentioning
confidence: 99%
“…Discussions on post-2020 biodiversity strategies by the signatory countries of the Convention on Biological Diversity (CBD) have led to proposals to declare a 'decade of restoration' in which rewilding will potentially be at the forefront of conservation policy, management and practice (Perino et al, 2019). Nevertheless, although there is significant growth in the use of the term in both academic and popular literature, its application and utility remains fundamentally contested (Anderson et al, 2019;Carey, 2016;Derham, 2019;Hayward et al, 2019;Lorimer et al, 2015;Pettorelli, Durant, & du Toit, 2019).…”
Section: Introductionmentioning
confidence: 99%